2020
DOI: 10.3389/fvets.2019.00504
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Staphylococcus aureus Detection From Clinical Mastitis Milk by Colloidal Gold Nanoparticle-Based Immunochromatographic Strips

Abstract: Rapid diagnostic technologies for bovine mastitis caused by Staphylococcus aureus (S. aureus) are urgently needed. In the current study, we generated an anti-ribosomal protein-L7/L12 antibody to detect S. aureus and an anti-ribosomal protein-L7/L12 antibody-coated immune-chromatographic strip (ICS) test. Moreover, we determined the ability of the ICS test to detect S. aureus from milk samples collected from cows with clinical mastitis. The developed ICS reacted to S. aureus in a bacteria load-dependent manner … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…In each case in which clinical mastitis was noticed, we aseptically collected a quarter milk sample before the administration of antibiotic treatment and stored the sample frozen at −20°C until ICS testing, somatic cell counting, and using the culture method. A previous study already confirmed that freezing and thawing of milk samples does not affect the ICS test score [ 15 ].…”
Section: Methodsmentioning
confidence: 63%
See 2 more Smart Citations
“…In each case in which clinical mastitis was noticed, we aseptically collected a quarter milk sample before the administration of antibiotic treatment and stored the sample frozen at −20°C until ICS testing, somatic cell counting, and using the culture method. A previous study already confirmed that freezing and thawing of milk samples does not affect the ICS test score [ 15 ].…”
Section: Methodsmentioning
confidence: 63%
“…As previously reported in our ICS test for S. aureus , we developed the ICS to detect RP-L7/L12 in E. coli and Klebsiella spp. etc., using colloidal gold-labeled antibodies, which are widely used for the construction of ICS tests [ 15 ]. Development of the ICS test was carried out based on the patent US 20190317093A1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ICS have also been developed for the detection of some bacterial pathogens, in particular foodborne pathogens and their toxins [ 46 ]. Development of ICS for the detection of human pathogens such as Mycobacterium tuberculosis [ 47 ], S. aureus [ 26 , 48 ], Helicobacter pylori [ 49 ], H. influenzae [ 50 ], and Neisseria gonorrhoeae [ 51 ] has been attempted, yet not as extensively as the previous applications.…”
Section: Discussionmentioning
confidence: 99%
“…A very recent study reported the development of an ICS for detecting S. aureus in milk samples [ 63 ]. However, they used a ribosomal protein as a target.…”
Section: Discussionmentioning
confidence: 99%